A Novel Bacteriophage with the Potential to Inhibit Fusobacterium nucleatum-Induced Proliferation of Colorectal Cancer Cells - Ho Yin Pekkle Lam; Meng-Jiun Lai; Pin-Chun Wang; Wen-Jui Wu; Li-Kuang Chen; Hsiang-Wei Fan; Chun-Chieh Tseng; Shih-Yi Peng; Kai-Chih Chang (Antibiotics)
Background: Increasing evidence shows that Fusobacterium nucleatum (F. nucleatum) largely affects colorectal cancer (CRC) growth and progression; therefore, the inhibition of intratumoral F. nucleatum may be one realistic approach to combat CRC. Although antibiotics are helpful in eliminating bacteria, the major problem remains the rise of potential antibiotic-resistant strains and antibiotic-associated adverse effects. Currently, bacteriophage therapy has gained interest because of its high selectivity to bacterial hosts and may become a realistic approach in treating bacteria-associated cancers. Methods: In this study, a new F. nucleatum bacteriophage, ØTCUFN3, was isolated and its biological characteristics were identified. In vitro and in vivo studies were performed to investigate the effect of ØTCUFN3 in combating F. nucleatum-induced CRC growth. Results: By applying ØTCUFN3 to F. nucleatum-induced CRC cell lines, p53+/+, and p53−/− isogenic HCT116 cells, our results revealed an inhibition of CRC proliferation and the expression of epithelial-to-mesenchymal transition (EMT) markers. ØTCUFN3 injection also reduced the growth of F. nucleatum-induced mouse xenografts. Conclusions: Our results demonstrated the use of F. nucleatum bacteriophage against CRC, laying the foundation for the future usage of bacteriophage in cancer treatment.